Electrochemically‐Assisted Low Power Density Laser Writing on Stainless Steel via Enrichment of Chromium Oxides - Zechariah J. Pfaffenberger; Lianlian Liu; Tae Kyong John Kim; Vignesh Venkataramani; Lydia Kisley (Advanced Materials Interfaces)
Abstract Laser color marking produces nearly permanent, environmentally friendly, vibrant colors on surfaces. However, previous work has used high‐power‐density pulsed lasers to induce the physicochemical reactions for marking. Here, laser color marking on stainless steel 304 (SS304) is performed with a less expensive continuous wave (CW) laser and a power density five orders of magnitude below that previously reported by combining an electrochemical cell with a fluorescence microscope. Using a combination of optical microscopy, x‐ray photoelectron spectroscopy, and bulk electrochemistry, it is demonstrated that the laser‐induced luminescence and colors are due to enrichment (32 ± 9% increase) of Cr2O3 in the SS304 passive film. It is shown that the enrichment proceeds by a different chemical mechanism than the oxygen pyrolysis that occurs in typical laser color marking. The technique provides a new pathway for laser color marking of metals in industrial settings with applications as diverse as solar absorbers or corrosion prevention.